Faktor Penentu Kinerja Keuangan Bank yang Terdaftar di BEI - Karnasi, Reniati; Lunarindiah, Gatri; Ramadhanti, Mutiara (DINASTI RESEARCH, 2025)
This study aims to analyze the impact of internal bank factors on profitability measured by Return on Assets (ROA) in conventional banks listed on the Indonesia Stock Exchange for the 2019-2023 period. The internal factors examined include capital adequacy ratio, credit risk, management efficiency, and liquidity risk. The research employs panel data using purposive sampling, involving 38 conventional banks. Data analysis was conducted using panel regression with the Fixed Effects Model (FEM). The results reveal that management efficiency has a significant negative effect on profitability, while liquidity risk has a significant positive effect. However, capital adequacy ratio and credit risk do not significantly affect profitability. This study highlights the importance of efficient operational management and optimal liquidity management in enhancing the financial performance of banks. The findings provide practical insights for bank management to effectively manage resources to support sustainable profitability.